Arginine as a regulator of antioxidant and gel formation in yak Myofibrillar proteins: Efficacy and mechanistic insights - Yuqi Wang; Yiwen Mei; Rongsheng Du; Shulin Zhang; Qiuyu Wang; Xiaofang Dao; Na Li; Lina Wang; Linlin Wang; Honghong He (Food Chemistry: X)
Arginine (Arg), a safe basic amino acid, modulates interprotein interactions and impacts the processing characteristics of myofibrillar proteins (MP) in meat products, as numerous studies have demonstrated. This study aimed to explore the effects of varying concentrations of Arg (0.025, 0.050, 0.100, 0.200 %) on the physicochemical properties and gel behavior of yak MP. Utilizing yak MP as the substrate, we assessed and analyzed the physicochemical attributes and gel performance of the MP-Arg composite system. The findings revealed that Arg facilitates MP unfolding and internal group exposure, effectively mitigating oxidative tertiary structure alterations. Arg exerts potent antioxidant activity on MP, augmenting their water-holding capacity, which ameliorates gel properties. In this experiment, 0.05 % Arg maximally inhibited oxidative damage to MP, with protection being concentration-dependent. Collectively, these findings suggest that Arg effectively inhibits the oxidative degradation of MP structure and promotes the formation of enhanced gel characteristics.